Endoscopic retrograde cholangiopancreatography using a cap-assisted highly flexible colonoscope in patients with Roux-en-Y anastomosis - Nakaji, So; Hirata, Nobuto; Yamauchi, Kenji; Shiratori, Toshiyasu; Kobayashi, Masayoshi; Fujii, Hiroyuki; Ishii, Eiji (Endoscopy, 2014)
In this retrospective study of 10 patients with Roux-en-Y anastomosis, endoscopic retrograde cholangiopancreatography (ERCP) using a cap-assisted thin highly flexible colonoscope was done for treatment of bile duct stones. In five patients, the papilla of Vater was successfully reached using the colonoscope alone. However, in the other five patients, combination with an overtube was needed to reach the papilla. In all cases, complete removal of bile duct stones was accomplished. Procedure-related adverse events occurred in two cases. In conclusion, use of a cap-assisted thin highly flexible colonoscope for ERCP was successful in patients with a Roux-en-Y anastomosis.